Tough and stretchable ionogels by in situ phase separation - Wang, Meixiang; Zhang, Pengyao; Shamsi, Mohammad; Thelen, Jacob L.; Qian, Wen; Truong, Vi Khanh; Ma, Jinwoo; Hu, Jian; Dickey, Michael D. (Nature materials, 2022)
Ionogels are compelling materials for technological devices due to their excellent ionic conductivity, thermal and electrochemical stability, and non-volatility. However, most existing ionogels suffer from low strength and toughness. Here, we report a simple one-step method to achieve ultra-tough and stretchable ionogels by randomly copolymerizing two common monomers with distinct solubility of the corresponding polymers in an ionic liquid. Copolymerization of acrylamide and acrylic acid in 1-ethyl-3-methylimidazolium ethyl sulfate results in a macroscopically homogeneous covalent network with in situ phase separation: a polymer-rich phase with hydrogen bonds that dissipate energy and toughen the ionogel; and an elastic solvent-rich phase that enables for large strain. These ionogels have high fracture strength (12.6 MPa), fracture energy (~24 kJ m −2 ) and Young’s modulus (46.5 MPa), while being highly stretchable (~600% strain) and having self-healing and shape-memory properties. This concept can be applied to other monomers and ionic liquids, offering a promising way to tune ionogel microstructure and properties in situ during one-step polymerization. Two monomers with distinct solubility of their corresponding polymers in an ionic liquid enable tuning of the microstructure of the copolymers during their polymerization. Thus, energy dissipative and elastic molecular domains are created, resulting in highly tough and stretchable ionogels.